Firm Performance and Financial Distress: The Moderation Role of Board Gender Diversity - Devi Wahyu Utami; Salma Ila Salsabila; Bagus Wahyu Widodo (Journal Governance Society, 2024)
This study contributes to the understanding of financial distress by examining the role of gender diversity on corporate boards as a moderating variable in the relationship between company performance and financial distress. Focusing on the property and real estate sector, the research utilized a sample of 120 observations collected through purposive sampling techniques. The analysis was conducted using regression techniques to assess the impact of board gender diversity while controlling for company performance. Findings reveal that neither company performance nor board gender diversity alone has a significant relationship with financial distress. However, the study highlights the importance of board gender diversity as a moderating factor, suggesting that the composition of the board can influence the dynamics between a company's performance and its susceptibility to financial distress. The practical implications of this research are particularly relevant for companies in the property and real estate sector, as it underscores the need for balanced gender representation on boards. It suggests that shareholders should take care when selecting new board members, ensuring a well-rounded mix of male and female directors. This diversity is valuable because it brings together different perspectives, experiences, and expertise that can enhance decision-making processes, potentially leading to better management of financial risks and overall company performance. Ultimately, this study advocates for a more inclusive approach to corporate governance that recognizes the benefits of gender diversity in the boardroom.